Ionic Transport Properties of Protonic Conducting Solid Biopolymer Electrolytes Based on Enhanced Carboxymethyl Cellulose - NH4Br with Glycerol - N. M. J., Rasali; A. S., Samsudin (Springer Berlin Heidelberg, 2018)
The present work investigates the ionic conductivity as well as its transport properties of carboxymethyl cellulose–NH4Br plasticized with various weight percentage of glycerol for solid biopolymer electrolytes (SBEs) prepared by solution-casting technique. It was shown from the FTIR analysis that the complexation transpires at C=O and C–O− from COO− of CMC upon the addition of glycerol into the SBEs system. The highest room temperature ionic conductivity of ~10−3 S cm−1 was achieved at 6 wt.% of glycerol owing to the broadening in the amorphous state as demonstrated in the XRD analysis. The conductivity-temperature plots were found to be in good agreement with the conventional Arrhenius relationship. It was further shown that the conducting element is mainly due to the protonation of H+ where ionic mobility and diffusion coefficient was found to contribute towards the enhancement in the ionic conductivity of SBEs system.